Adjectives as saturators vs. modifiers: Statistical evidence - Boleda, Gemma; Evert, Stefan; Gehrke, Berit; McNally, Louise (Proceedings of the Amsterdam Colloquium, 2011)
This paper reports on a large-scale, statistical analysis of corpus data to support the null hypothesis that ethnic adjectives (EAs, e.g. French) are ordinary adjectives, rather than argument-saturating “nouns in disguise” (in, e.g., French agreement). In particular, EAs are argued to simply modify the noun they combine with, so that their special properties in inducing argument-like behavior arises from the interaction between the semantics of event nominals and that of the adjective.